2001
DOI: 10.1002/1522-2640(200105)73:5<461::aid-cite461>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Sol-Gel Synthesis and Spray Granulation of Porous Titania Powder

Abstract: Bimodally porous titania powders with controlled phase composition and porosity made by wet chemical processes have been extensively investigated in our laboratory. This paper reviews experimental parameters affecting the phase and pore structure of these powders. Also, the effect of solution peptization on packing and coordination of particles is discussed. The unpeptized slurry and peptized sol were spray dried to make granules with controlled porosity and morphology. The properties of the product granules w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
1
3
0
1
Order By: Relevance
“…3 and Table 2): a) with increasing calcination temperature the average aggregate size increased, b) with increasing average aggregate size, the SSA decreased and c) the addition of Zr increased the SSA. This is in excellent agreement with Kim et al [19] who found that Zr addition had a positive effect on the stabilization of pore structure.…”
Section: Effect Of Zr Doping Concentration On Ntio2 Structuresupporting
confidence: 92%
See 1 more Smart Citation
“…3 and Table 2): a) with increasing calcination temperature the average aggregate size increased, b) with increasing average aggregate size, the SSA decreased and c) the addition of Zr increased the SSA. This is in excellent agreement with Kim et al [19] who found that Zr addition had a positive effect on the stabilization of pore structure.…”
Section: Effect Of Zr Doping Concentration On Ntio2 Structuresupporting
confidence: 92%
“…For sol-gel synthesized nTiO2 powders, Kim et al [19] found a bimodal porosity which consists of large intra-NP pores in the order of ~50-100 nm (due to voids between NPs making up the aggregates) and small pores of 2-5 nm within the NPs (the NPs are composed of crystallites). Zr-doping allowed maintaining pore populations up to relatively high calcination temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Die Darstellung von nanoskaligem Titan(IV)oxid erfolgt durch Umsetzung von Tetra-isopropyl-orthotitanat in einer salpetersauren wässrigen Lösung [1]. Anschlieûend werden die entstandenen Präzipitate über ein Zeitraum von 24 Stunden peptisiert.…”
Section: K102unclassified
“…Some of the unpeptized and peptized samples were dried at 110°C, then calcined at different temperatures, to allow comparison with the spray-dried samples. 17 Alumina-and zirconia-doped titania sols were also synthesized by the cohydrolysis and condensation of TTIP and dopants of aluminum tri-sec-butoxide (ATSB, Al(OC 4 H 9 ) 3 , 97%; Aldrich) or zirconium n-propoxide (ZNP, Zr(OC 3 H 7 ) 4 , 70%; Fluka Chemical Corp., Ronkonkoma, NY). First, the TTIP was dissolved in anhydrous ethyl alcohol, as described above.…”
Section: (1) Preparation Of Feed Solutionsmentioning
confidence: 99%
“…Thus, the peptized titania granules and the powders exhibited a similar tendency in SSA. 17 The small difference in SSA values can be attributed to the different geometries of the two samples. The peptized titania granules had a largely spherical shape, whereas the peptized titania powders were flakelike.…”
Section: December 2001mentioning
confidence: 99%